Development of Electronic Modules Using The Canva Application Assisted With Quizizz in Learning Achievements Basic Accounting Principles and Concepts - Widiastuti, Ayu; Widayati, Ani (Universitas Pendidikan Ganesha, 2024)
The objectives of this research are: (1) creating learning media in the form of electronic modules for students; (2) explaining the feasibility of learning media in the form of electronic modules created based on the opinions of material experts and media experts; (3) revealing the practicality of learning media in the form of electronic modules based on the opinions of educational practitioners/teachers and users/students. This research is development research using the ADDIE development model. The test subjects in this research were classes X AKL1 and X AKL2 at Muhammadiyah Dukun Vocational School. Data was collected through observation and questionnaires. This research uses quantitative descriptive analysis. The data collection instrument used was a verification questionnaire from material expert validators, media expert validators, teachers, and student responses. Development products are assessed for content suitability, presentation suitability, linguistic suitability, and contextual suitability by material expert validators; graphic suitability by media expert validators; and practicality by teachers and students. The results of this research are as follows: (1) The learning media is in the form of electronic modules with the Canva application assisted by Quizzizz in learning outcomes of basic accounting principles and concepts. (2) This electronic module was declared feasible by material experts with a content suitability score of 3.83, presentation suitability 3.75, language suitability 3.82, contextual suitability 3.89, and declared feasible by media experts with a graphic suitability score of 3.62. (3) This electronic module product was declared practical by the teacher with a percentage of 92.3% and practicality for students with a percentage of 94% with very practical criteria.